The Canonization Process of the Masoretic Text. Issue 2 (August 2016) - Sipilä, Seppo
This article discusses the process that gave canonical status to the Masoretic Text. The discussion will start from the present reality and continue backwards. Because the Masoretic Text is a creation of rabbinic Judaism and because the rabbis did discuss the status of various books within the Masoretic Text, this article will argue for a late dating both of the text as a collection and of its canonization. However, within Christian canons, the Masoretic Text acts as a canonical text in a limited way, in the sense that it is only a part of those canons. Besides, there is no moment in history where any authority declared the Masoretic Text canonical. Therefore, it is nowadays widely accepted as a canonical text, but without authorization.